Role of glycemic control in patients with type 2 diabetes mellitus - Konstantin V. Ovsyannikov; Evgeny A. Praskurnichiy (LLC "MEDIAFORMAT", 2023)
It is well-known that patients with type 1 and 2 diabetes mellitus are at high risk of complications of micro- and macrovascular disease. Furthermore, the relationship between elevated blood glucose levels and microvascular complications is likely to be direct and is generally specific for diabetes. However, the correlation with macrovascular risk is more complex, multifactorial and not limited to hyperglycemia only. The paper considers the relationship between the macro- and microvascular damage to the target organs associated with DM and cardiovascular risk. The review of studies focused on assessing the effectiveness of blood glucose level reduction in type 2 diabetes mellitus in the context of cardiovascular safety is provided. Advanced DM treatment methods are discussed. Special attention is paid to self-monitoring of blood glucose as one of the most important factors of the DM management and prevention of complications.